TEORI POSTUR MOTIVASI DALAM STUDI EKSPERIMEN KEPUTUSAN KEPATUHAN PAJAK DI INDONESIA (Proceeding Fakultas Ekonomi, 2015)
This study used motivational posture theory to examine the effect of individual posture motivational taxpayer's as internal factors of the tax compliance decision. While external factors of taxpayer in this study is the audit strategy and the amount of tax exemption (taxable income).  An external factor of taxpayer as an independent variable in this study is an experimental variable. Tax audit strategy divided into two levels of treatment, the tax audit strategy of fixed and random. The amount of taxable income is divided into two levels of treatment, that is taxable income go up and down. While the internal factors of motivation posture placed as a covariate variable on the dependent variable tax compliance  decisions.  Based  on  the  number  of  independent  variables  and  treatment  as  well  as treatment  of  the  participants,  the  design  used  in  this  study  was  Quasi  Experimental  Design Between-Subject 2X2 with Covariate with random assignment method. The subjects in this experiment are an individual taxpayer who has a tax ID, doing their own business and have experience in reporting their tax revenue. The analysis technique used was Analysis of Covariate. The results showed that the posture motivation of Indonesian taxpayer’s as concomitant factors does not affect tax compliance decisions. This is not accordance with Motivational Posture Theory. This study proves that the tax audit strategy and the amount of taxable income affect tax compliance decisions. The taxpayer is given the treatment of fixed audit strategy will be more compliant than the taxpayer is given random audit strategy. The amount of taxable income that rises will lead to decisions that tax compliance is higher when compared with the taxable income down. This study contributes to the novelty of tax compliance research in terms of the implications of the theory, the variable placement and research design.       Keywords: tax compliance decisions, motivational postures, strategy of tax audit, taxable income.